Susceptibility locus for lung cancer at 15q25.1 is not associated with risk of pancreatic cancer - Chen, Jinyun (2011)
OBJECTIVES: Four genome-wide association (GWA) studies have found that variation in a region of strong linkage disequilibrium on the long arm of chromosome 15 (15q24-25.1), containing nicotinic acetylcholine receptor genes, contributes to lung cancer risk. Since cigarette smoking is a major risk factor for developing both lung cancer and pancreatic cancer, we hypothesized that variation in this region may also modify individual susceptibility to pancreatic cancer. METHODS: We conducted a case-control study of 532 patients with pathologically confirmed pancreatic adenocarcinoma and 1046 age-, sex-, ethnicity-, and smoking behavior-matched cancer-free controls. RESULTS: We found that the two risk single nucleotide polymorphisms (SNPs) reported in the lung cancer GWA studies, rs8034191: A>G and rs1051730: G>A, located in this 15q24-25.1 region, were not associated with risk of pancreatic cancer. CONCLUSIONS: The results of our study suggest that the two SNPs at 15q25.1 do not modify pancreatic cancer risk.